2020
DOI: 10.1155/2020/5272130
|View full text |Cite
|
Sign up to set email alerts
|

High Burden among Older Family Caregivers is Associated with High Prevalence of Symptoms: Data from the Swedish Study “Good Aging in Skåne (GÅS)”

Abstract: Background/Aim. Certain groups of informal caregivers have been shown to have worse health compared to noncaregivers. The aim of this cross-sectional study was to explore the health and gender aspects of caregiving in an older Swedish population. Methods. Our study included 5457 participants from the longitudinal, general population study “Good Aging in Skåne.” A total of 33 self-reported symptoms were obtained from questionnaires and were then divided into seven domains: depressive, musculoskeletal, gastrouri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 38 publications
3
15
0
1
Order By: Relevance
“…In our study female WKCs more often than males provided care alone across most care domains such as personal care, physical activities, medication, and contact with services. These findings correspond with the existing literature on the role of female informal carers in providing personal care and more complex care activities [ 53 , 54 ], compared to male informal carers who, more commonly, support the care-receiver´s instrumental activities and provide financial support[ 55 , 56 ].…”
Section: Discussionsupporting
confidence: 88%
“…In our study female WKCs more often than males provided care alone across most care domains such as personal care, physical activities, medication, and contact with services. These findings correspond with the existing literature on the role of female informal carers in providing personal care and more complex care activities [ 53 , 54 ], compared to male informal carers who, more commonly, support the care-receiver´s instrumental activities and provide financial support[ 55 , 56 ].…”
Section: Discussionsupporting
confidence: 88%
“…This finding is in agreement with that ofEkström et al 15 who studiedhigh burden among older family caregivers is associated withhigh prevalence of symptoms: data from the Swedish Study "Good Aging in Skane (GAS)". Where they concluded that, more than one third of caregivers were with low educational level.…”
Section: Resultssupporting
confidence: 92%
“…Other studies defend that COVID-19 pandemic and the lockdown increased the levels of depression rather than of anxiety [13]. These findings are of concern to health professionals and a lot of studies note the negative effect of anxiety on caregiver burnout [14,15], which is reported in a considerable percentage of dementia caregivers [16], being the female sex a risk factor not only for becoming a caregiver but also for experiencing caregiving as a burden [17,18]. Also, our results showed that caregivers often feel frustrated when they do not have social and/or family support and, this is similar to the findings of Canevelli et al [12], where caregivers complain of having poor support in the most difficult moments, with the consequent feeling of loneliness and isolation in 54% of cases.…”
Section: Discussionmentioning
confidence: 99%